2007
DOI: 10.1007/s00277-007-0406-3
|View full text |Cite
|
Sign up to set email alerts
|

Measuring holotranscobalamin II, an early indicator of negative vitamin B12 balance, by radioimmunoassay in patients with ischemic cerebrovascular disease

Abstract: Circulating homocysteine is a risk factor of cardiovascular and cerebrovascular events. Hyperhomocysteinemia may be an early indicator for vitamin B12 disorders because cobalamin is a cofactor in the remethylation process of homocysteine. Serum holotranscobalamin (holoTC II) becomes decreased before the development of metabolic dysfunction. In this study, we assessed circulating holoTC II to estimate the diagnosis of vitamin B12 deficiency in the first ischemic cerebrovascular attack. We also compared the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In the absence of a gold standard to detect vitamin B12 deficiency, the current laboratory tests to measure serum vitamin B12 levels may not be able to diagnose vitamin B12 deficiency in the early stages [1,[12][13][14][15]. The findings from several studies performed in different clinical settings have confirmed that serum vitamin B12 is a relatively poor marker with low sensitivity and specificity in predicting vitamin B12 status and that holoTC is a useful diagnostic indicator for this purpose [3,5].…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…In the absence of a gold standard to detect vitamin B12 deficiency, the current laboratory tests to measure serum vitamin B12 levels may not be able to diagnose vitamin B12 deficiency in the early stages [1,[12][13][14][15]. The findings from several studies performed in different clinical settings have confirmed that serum vitamin B12 is a relatively poor marker with low sensitivity and specificity in predicting vitamin B12 status and that holoTC is a useful diagnostic indicator for this purpose [3,5].…”
mentioning
confidence: 87%
“…The symptoms of vitamin B12 deficiency are variable, and these symptoms may be easily missed, particularly if the serum vitamin B12 levels are within the normal range [12,13]. In the absence of a gold standard to detect vitamin B12 deficiency, the current laboratory tests to measure serum vitamin B12 levels may not be able to diagnose vitamin B12 deficiency in the early stages [1,[12][13][14][15].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Transcobalamin is essential for the transport of vitamin B12 from the intestine into most cells of the body, and patients lacking this protein eventually develop vitamin B12 deficiency [ 6 ]. When vitamin B12 is bound to transcobalamin, it is termed holoTC and represents the biologically active fraction of vitamin B12 that can be delivered to all DNA-synthesizing cells.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B12 is essential for cellular metabolism, particularly for DNA synthesis and both fatty acid and amino acid metabolism. Importantly, vitamin B12 is a cofactor in homocysteine metabolism, and its deficiency may be an important cause of hyperhomocysteinemia [ 6 , 7 ], which is closely correlated to the risk of ischemic stroke as a result of the increased development of carotid plaques [ 2 ]. Vitamin B12 supplementation may contribute to stroke prevention [ 8 ], thus lowering homocysteine levels.…”
Section: Introductionmentioning
confidence: 99%